Organization of audit in the sphere of administrative informational systems - Мац, Т. П.; Левченко, З. М. (Scientific Progress & Innovations, 2014)
Generalized and systematic approach of local scientists and foreign scientists on the organization of the audit. The definition of audit based on the analysis of the main components of organizational performance that is based on management information systems and technologies. Taking into account the specific features of the audit, its types and purposes of implementation, we proposed components of the audit process. In this case, the internal and external processes related to the organization of the audit can be implemented by various electronic means.